Edukasi Kebijakan Dan Sistem Kesehatan Nasional Bagi Masyarakat Desa (2025) - Nana Erika; Rina Anggraini; Nabila Keysa (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2025)
Increasing rural communities’ understanding of national health policy and system is a strategic step toward improving access and equality in Indonesia’s health services. Health policy education plays a crucial role in ensuring that citizens understand their rights and responsibilities as National Health Insurance (JKN) participants, as well as the mechanisms of available healthcare services. This study aims to analyze the effectiveness of health policy education in rural areas, focusing on the improvement of health literacy, community participation in decision-making, and the role of health workers as facilitators. A descriptive quantitative method was applied through surveys and field observations in three villages of Sleman Regency, Yogyakarta. The findings reveal that 82% of respondents understood their JKN rights after the education program, compared to only 45% before. Major challenges included limited information media and low digital literacy among villagers. The study concludes that community education on national health policy effectively enhances public awareness of universal health coverage but requires continuous support through collaboration between local government, healthcare providers, and educational institutions.